SEKOLAH MENENGAH ATAS (SMA) NEGERI 10 KERINCI : DARI SMU RABIAH BULAN HINGGA SMAN 10 KERINCI (2003-2021) - Najmi Najmi; Dian Anisa Fitri (Ensiklopedia Education Review, 2022)
This article describes the development of an educational institution, namely SMA Negeri 10 Kerinci, previously known as SMU Rabiah Bulan. The research method used is the historical method through library research, archives and field studies to obtain data, then source criticism, namely internal and external criticism, is carried out in order to classify the data that has been obtained and then interpret it for historiography preparation. The findings of the article show that SMA Negeri 10 Kerinci is a high school that has rapid development and is able to compete with high schools that have been established previously. Established in 2003 under the auspices of the Putri Rabiah Bulan Foundation with an operational permit from the Kerinci District Education Office on September 15, 2003. It officially became a public school with a decree from the Regent of Kerinci dated February 28, 2005. It became SMA Negeri 2 Gunung Raya. Based on the Decree of the Regent of Kerinci dated July 27, 2010, the School Nomenclature was changed to SMA Negeri 10 Kerinci.Keywords:Development, Institution, School